The Influence Of Brand Awareness On Purchasing Decisions With User Generated Content As A Moderating Variable: Penelitian - Anshar Daud; Wandi Janwar; Yusniar; Syifa Pramudita Faddila; Mohammad Azharie Hamdany (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is a quantitative research with an explanatory approach.. The data used in this study is primary data that the researcher obtained directly from various sources or commonly referred to as primary sources from 295 Pose sandal customers spread throughout Indonesia. The data obtained by the researcher was analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the Brand Awareness variable can have a positive relationship direction and a significant influence on Purchasing Decisions because the P-Values ​​value is positive and below the 0.05 significance level, namely 0.001. T. The result of the P-Values ​​value of 0.001 means that Brand Awareness can make a product more famous, widen the product's market share, and ultimately can influence Purchasing Decisions. In addition, the User Generated Content variable can also moderate the influence of the Brand Awareness variable on Purchasing Decisions because the P-Values ​​value also tends to be positive and is below the 0.05 significance level, namely 0.000. Thus, it can be concluded that the first and second hypotheses in this article can be accepted.